1995
DOI: 10.1002/hep.1840220311
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled trial of ursodeoxycholic acid in primary biliary cirrhosis

Abstract: One hundred fifty-one patients with primary biliary cirrhosis (PBC) grouped into four strata based on entry serum bilirubin ( < 2 mg/dL vs. 2 md/dL or greater) and liver histology (stages I, II vs. stages III, IV-Ludwig criteria) were randomized within each stratum to ursodiol or placebo given in a single dose of 10 to 12 mg/kg at bedtime for 2 years. Placebo- (n = 74) and ursodiol- treated (n = 77) patients were well matched at baseline for demographic and prognostic factors. Ursodiol induced major improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
117
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(125 citation statements)
references
References 8 publications
5
117
0
3
Order By: Relevance
“…UDCA has been shown to improve liver function tests, liver histology, and survival in primary biliary cirrhosis, [1][2][3][4][5][6] and similar effects have been observed in other cholestatic diseases. [7][8][9][10][11][12][23][24][25] The mechanism of action of UDCA in hepatobiliary diseases is still not completely understood.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…UDCA has been shown to improve liver function tests, liver histology, and survival in primary biliary cirrhosis, [1][2][3][4][5][6] and similar effects have been observed in other cholestatic diseases. [7][8][9][10][11][12][23][24][25] The mechanism of action of UDCA in hepatobiliary diseases is still not completely understood.…”
Section: Discussionmentioning
confidence: 61%
“…In primary biliary cirrhosis, UDCA treatment slows progression of the disease and improves survival. [1][2][3][4][5][6] In primary sclerosing cholangitis (PSC), UDCA improves laboratory parameters, [7][8][9][10][11][12] and its effect on the outcome is currently being evaluated. There is evidence 11,12 that high doses (Ն20 mg/kg/d) of UDCA may be more effective than average doses (15 mg/kg/d).…”
mentioning
confidence: 99%
“…63 However, the combined analysis of the other 3 large studies does not suggest that this is the case. 64 In fact, the greatest benefit is seen in those with the most severe disease, because predictably, more events were observed in patients with severe rather than with mild disease.…”
Section: Ursodeoxycholic Acid Therapymentioning
confidence: 96%
“…60 There have been many randomized controlled trials of UDCA in PBC and all included both asymptomatic and symptomatic patients. There have been 4 large trials, 32,[61][62][63] and the raw data from 3 of these trials have been combined as each used the same formulation of UDCA in the same dose, i.e., 13 to 15 mg/kg/d. 64 The analysis of these data collected from 548 patients shows that UDCA therapy leads to a significant increase in survival after up to 4 years of therapy, as judged by time to liver transplantation.…”
Section: Ursodeoxycholic Acid Therapymentioning
confidence: 99%
“…[1][2][3][4] In addition, a combined analysis, pooling 548 patients involved in three large trials using a similar dose of UDCA, has demonstrated that 4-year UDCA therapy increases survival free of orthotopic liver transplantation (OLT). 5 In untreated patients with PBC, elevated levels of serum bilirubin level (SBL) have been consistently found to be an independent predictor of a poor prognosis.…”
mentioning
confidence: 99%